Literature and nationalist ideology: writing histories of modern Indian languages - Harder, Hans (Social Science Press, 2010)
Contributed papers presented at a conference
Keywords: Konferenzschrift -- 2006 -- Halle; Nationalismus; Literaturgeschichtsschreibung; Indische Sprachen; Literatur; Indien